EORTC consensus recommendations on the optimal management of colorectal cancer liver metastases - Bregni, Giacomo; Adams, Richard; Bale, Reto; Bali, Maria A; Bargellini, Irene; Blomqvist, Lennart; Brown, Gina; Cremolini, Chiara; Demetter, Pieter; Denecke, Timm; Dohan, Anthony; Dopazo, Cristina; et al. (Cancer treatment reviews, 2025)
•The optimal management of colorectal cancer liver metastases is a matter of debate•The EORTC GITCG promoted the development of a European consensus on this subject•A multidisciplinary team of 43 international experts participated to a Delphi survey•34 practical recommendations and 2 consensus statements were proposed•This document provides clinical guidance and highlights grey areas and unmet needs Patients with colorectal cancer liver metastases have long represented a unique and thoroughly investigated population. Nevertheless, the optimal management of these is still controversial with a number of open questions which are only partially addressed by available studies and existing guidelines. The European Organisation for Research and Treatment of Cancer (EORTC) Gastrointestinal Tract Cancer Group (GITCG) sought to fill this knowledge gap and promoted the development of a European consensus on this subject. By using the Delphi methodology and leveraging a multidisciplinary team of 43 international experts, including gastrointestinal oncologists, hepatobiliary surgeons, interventional radiologists, radiation oncologists, radiologists, nuclear medicine physicians and pathologists from 12 European countries, 34 practical recommendations and two consensus statements were proposed. These cover varying aspects of the optimal management of colorectal cancer liver metastases such as baseline imaging, selection criteria for liver-directed therapies, treatment strategies, assessment of treatment response, follow-up, care delivery, clinical research and future perspectives. This roadmap document is intended to complement national and international guidelines, and to provide practical guidance for clinicians and multidisciplinary teams, ultimately promoting practice standardisation, optimal management and better patient outcomes across Europe. Also, it provides a unique opportunity to highlight grey areas and unmet needs, and to give a strategic direction to future research in the field by identifying topics where there is no consensus among experts.